UNDERSTANDING OF VISIONARY LEADERSHIP AND LEADERSHIP ETHICS IN ORGANIZATIONS: QUALITATIVE STUDY - Putri, Aufa Qinni Kendalla; Putri, Fathiya Annisa; Eryanto, Henry; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This research aims to explain in depth the practice of visionary leadership and leadership ethics in the context of companies operating in the service sector and general suppliers. This research uses a qualitative approach with a case study research design in companies located in the West Jakarta area, Indonesia. Data collection uses interview techniques, observation and documentation studies. The research results show that the visionary leadership applied by the leadership is demonstrated by skills in formulating a vision and translating it to the staff. The leadership also tries to establish active cooperation with the company staff. In the short term, ethical leaders can help improve employee morale and help them feel good about management and their work. The research findings provide information that can be used as evaluation material in the implementation of visionary leadership which is also based on leadership ethics for company leaders.